Assessment and Management of Older Patients With Transthyretin Amyloidosis Cardiomyopathy: Geriatric Cardiology, Frailty Assessment and Beyond - Irabor, Biobelemoye; McMillan, Jacqueline M.; Fine, Nowell M. (Frontiers in Cardiovascular Medicine, 2022)
Transthyretin amyloidosis cardiomyopathy (ATTR-CM) is commonly diagnosed in older adults, in particular the wild-type (ATTRwt), which is regarded as an age-related disease. With an aging population and improved diagnostic techniques, the prevalence and incidence of ATTR-CM will continue to increase. With increased availability of mortality reducing ATTR-CM therapies, patients are living longer. The predominant clinical manifestation of ATTR-CM is heart failure, while other cardiovascular manifestations include arrhythmia and aortic stenosis. Given their older age at diagnosis, patients often present with multiple age-related comorbidities, some of which can be exacerbated by ATTR, including neurologic, musculoskeletal, and gastrointestinal problems. Considerations related to older patient care, such as frailty, cognitive decline, polypharmacy, falls/mobility, functional capacity, caregiver support, living environment, quality of life and goals care are particularly important for many patients with ATTR-CM. Furthermore, the high cost ATTR treatments has increased interest in establishing improved predictors of response to therapy, with assessment of frailty emerging as a potentially important determinant. Multidisciplinary care inclusive of collaboration with geriatric and elder care medicine specialists, and others such as neurology, orthopedics and transcatheter aortic valve replacement clinics, is now an important component of ATTR-CM management. This review will examine current aspects of the management of older ATTR-CM patients, including shared care with multiple medical specialists, the emerging importance of frailty assessment and other considerations for using ATTR therapies.